Flood model of the deepest cave in the world - Kavaliauskas, Mindaugas (Lietuvos matematikos rinkinys, 2010)
Lithuanian speleology expedition to the Krubera-Voronya cave, the deepest known cave in the world, was organized in summer of 2009. The data from water lever logger devices was read. Data of cave water level and meteorologic data is analysed. Mathematical model of water level is proposed. This work should help to predict caves flooding and increase safety of speleological expeditions.